2014
DOI: 10.1016/j.virol.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration is another player of the minute virus of mice infection

Abstract: The parvovirus minute virus of mice, prototype strain (MVMp), preferentially infects and kills cancer cells. This intrinsic MVMp oncotropism may depend in part on the early stages of MVMp infection. To test this hypothesis, we investigated the early events of MVMp infection in mouse LA9 fibroblasts and a highly invasive mouse mammary tumor cell line derived from polyomavirus middle T antigen-mediated transformation. Using a combination of fluorescence and electron microscopy, we found that various parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It has recently been shown that one of those factors is an enhanced virus uptake in cancer cells. Cell migration, which is typically associated with some aggressive cancer cells, promotes MVMp uptake [ 65 ]. Another finding establishing a correlation between MVMp uptake and cancer cells is the requirement of MVMp for galectin-3, a multifunctional protein implicated in cancer metastasis.…”
Section: Uptake Into Host Cellsmentioning
confidence: 99%
“…It has recently been shown that one of those factors is an enhanced virus uptake in cancer cells. Cell migration, which is typically associated with some aggressive cancer cells, promotes MVMp uptake [ 65 ]. Another finding establishing a correlation between MVMp uptake and cancer cells is the requirement of MVMp for galectin-3, a multifunctional protein implicated in cancer metastasis.…”
Section: Uptake Into Host Cellsmentioning
confidence: 99%
“…Here, we went one step further as we identified a 5-protein classifier (FAK, N-cadherin, E-cadherin, β-catenin, Snail) that predicts response to MVMp virotherapy in murine PDAC models. We speculate that MVMp hijacks the uptake and lysosomal/proteasomal degradation of expired focal-adhesion molecules that are generated following physical tension of stress fibers, during the very dynamic process of mesenchymal cell migration, as previously described 16 We also established an instructive role of this classifier in predicting MVMp lytic efficacy in patient-derived primary pancreatic tumor cells, albeit the "mesenchymal status" does not perfectly match the classical/basal-like molecular subtyping found in the literature 22 . Here, Slug expression seems not to be as important as in murine PDAC cells to predict MVMp efficacy.…”
Section: Discussionmentioning
confidence: 55%
“…The present study illustrates for the first time the high selectivity of MVMp oncolytic virus for a particular subtype of PDAC, a disease with no cure that highly resist to conventional therapies. MVMp was previously found to enter leading edge of migrating cells by endocytosis close to filopodial and focal adhesions areas, notably following induction of EMT 16 . Interestingly, two main molecular subtypes have been recently described in PDAC, including the classical/pancreatic progenitor subtype associated with a better prognosis, and the Basal-like/Squamous subtype associated with resistance to treatment and poorer clinical prognosis, including immune escape 20 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The minute virus of mice is a small, non-enveloped, single-stranded DNA virus from the Parvoviridae family, known for its oncotropic properties, infecting and killing cancer cells [106]. A study examining Gal-3 and N-acetylglucosaminyltransferase V (Mgat5) in MVM infection found that both are crucial for efficient cell entry and infection, with cancer cells expressing higher levels of Gal-3 being more susceptible to MVM infection [107].…”
Section: Minute Virus Of Micementioning
confidence: 99%